Analysis of Teachers’ Teaching Methods to see Students ’ Learning Motivation in Pancasila Education Subjects in Elementary School - Ilmi, Najwa (International Journal of Students Education, 2024)
This study aims to analyze the teaching methods employed by teachers to assess student motivation in learning the subject of Civic Education (Pancasila Education) at the elementary school level (SD), using a literature review research method. The primary focus of this study is to explore various strategies and approaches used by teachers to enhance student motivation, as well as to understand their impact on the understanding and application of Pancasila values among students. The data used in this research are drawn from various literature sources related to motivation theory, active learning approaches, and character education within the context of Civic Education. The findings of this study reveal that the use of varied teaching methods, such as group discussions, educational games, and creative assignments, can enhance students’ intrinsic motivation, making them more engaged and active in class. Additionally, the teacher’s role as a motivator, facilitator, and role model in instilling Pancasila values is identified as a key factor in fostering sustained learning motivation. This research is expected to provide insights for educators and education managers in designing more effective teaching strategies to improve student motivation in the context of Civic Education.